2015
DOI: 10.1111/apha.12578
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and cardioprotective effects of the dipeptide isoleucine–tryptophan and whey protein hydrolysate

Abstract: Whey protein hydrolysate and isoleucine-tryptophan powerfully inhibit plasma ACE resulting in antihypertensive effects. Moreover, isoleucine-tryptophan blunts tissue ACE activity, reduces matrix metalloproteinase-2 activity and improves coronary flow reserve. Thus, whey protein hydrolysate and particularly isoleucine-tryptophan may serve as innovative food additives with the goal of attenuating hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…After oral IW intake for 14 weeks, the pathological rise of systolic arterial blood pressure in spontaneously hypertensive rats was effectively prevented [20]. This antihypertensive effect of IW was associated with decreased ACE activity and minimized myocardial remodeling [20]. As shown in previous studies, IW inhibits systemic ACE and also local tissue ACE activity [20,21], which plays a prominent role in vascular remodeling and cardiovascular homeostasis [6,22].…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…After oral IW intake for 14 weeks, the pathological rise of systolic arterial blood pressure in spontaneously hypertensive rats was effectively prevented [20]. This antihypertensive effect of IW was associated with decreased ACE activity and minimized myocardial remodeling [20]. As shown in previous studies, IW inhibits systemic ACE and also local tissue ACE activity [20,21], which plays a prominent role in vascular remodeling and cardiovascular homeostasis [6,22].…”
mentioning
confidence: 74%
“…This antihypertensive effect of IW was associated with decreased ACE activity and minimized myocardial remodeling [20]. As shown in previous studies, IW inhibits systemic ACE and also local tissue ACE activity [20,21], which plays a prominent role in vascular remodeling and cardiovascular homeostasis [6,22]. Evidence for ACE inhibition by IW in humans was provided by Kaiser et al [23], who reported a transient rise of IW plasma concentrations after oral intake that was correlated with reduced plasma ACE activity [23].…”
mentioning
confidence: 84%
“…The effect on blood pressure of ACE‐inhibiting peptides derived from food proteins was investigated in a SHR rat model by Martin et al . The group finds that isoleucine‐tryptophan blunts tissue ACE activity, reduces matrix metalloproteinase‐2 activity and improves coronary flow reserve.…”
mentioning
confidence: 99%
“…The group finds that isoleucine‐tryptophan blunts tissue ACE activity, reduces matrix metalloproteinase‐2 activity and improves coronary flow reserve. These fascinating findings may suggest that whey protein hydrolysate may serve as innovative food additives in the fight against arterial blood pressure …”
mentioning
confidence: 99%
“…The obesity epidemic has reached endemic proportions, and excellent studies are needed to help us understand foetal programming and pathophysiology of metabolic syndrome and its related disorders. Dietary supplements have repeatedly been at the centre of interest at our journal …”
mentioning
confidence: 99%